2012
DOI: 10.1108/jcre-12-2012-0030
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of organizational relocation: a conceptual framework

Abstract: Purpose -Relocation is a significant event in the course of an organization's lifetime. The purpose of this paper is to focus on the impacts that relocation has on the relocating organization itself and to identify the economic, social, and environmental impacts of office occupier relocation. Design/methodology/approach -Drawing from the existing literature on impacts of occupiers' relocation, a conceptual framework for modelling organizational relocation impacts is developed. The literature review is done by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 59 publications
0
63
0
Order By: Relevance
“…Due to change of location, one of the possible impacts of relocation is the changed commuting (Christersson and Rothe 2012). Krausz, Bizman and Fox (2002) found that perceived changes in commuting were significantly related to relocation satisfaction.…”
Section: Pre-move Research Hypothesesmentioning
confidence: 98%
See 3 more Smart Citations
“…Due to change of location, one of the possible impacts of relocation is the changed commuting (Christersson and Rothe 2012). Krausz, Bizman and Fox (2002) found that perceived changes in commuting were significantly related to relocation satisfaction.…”
Section: Pre-move Research Hypothesesmentioning
confidence: 98%
“…Krausz, Bizman and Fox (2002) addressed perceived changes in various organisational dimensions after relocation. Christersson and Rothe (2012) maintain that two of the main factors from which the relocation impacts derive are the location change (old versus new) and the building change (old versus new). Accordingly, two perceived changes related to the location (accessibility of the behavioural sciences school site, and the school site's surroundings) were examined.…”
Section: Pre-move Research Hypothesesmentioning
confidence: 98%
See 2 more Smart Citations
“…They are critical yet potentially stressful events (Peach et al, 2005) for organizations and there can be a variety of economic, social and environmental impacts due to the relocation (see e.g. a framework developed by Christersson and Rothe, 2012). These impacts can derive from the relocation management, or location, building, or workplace changes.…”
Section: Introductionmentioning
confidence: 99%